Integrating Occupational Health and Safety into Enterprise Risk Management: a structural evaluation - Yalçın Kılıç; Özalp Vayvay (Frontiers in Public Health, 2025)
IntroductionThis study aims to investigate the extent to which Occupational Health and Safety (OHS) risks can be incorporated into the broader framework of Enterprise Risk Management (ERM). Although both systems were developed with similar goals—identifying, assessing, and mitigating risks—they have often operated independently. The research explores whether aligning OHS practices with ERM strategies, particularly through internal audit mechanisms, can foster a more unified and efficient approach to organizational risk management.MethodA qualitative document analysis was conducted, examining current national legislation, international standards such as ISO 31000 (Risk Management) and ISO 45001 (Occupational Health and Safety), and selected academic studies. The evaluation focused on structural similarities, procedural intersections, and the functional roles of personnel involved in ERM, Internal Audit (IA), and OHS processes.ResultsThe analysis revealed a substantial convergence between ERM and OHS in terms of risk identification techniques, prevention-based methodologies, and monitoring processes. The responsibilities of internal auditors and occupational safety specialists display notable overlaps, particularly in areas such as compliance, documentation, hazard assessment, and performance reporting. These parallels support the feasibility of integrating OHS risk management into the ERM structure.ConclusionFor a more effective and holistic approach to enterprise-level risk governance, it is essential to include Occupational Health and Safety risks within the ERM framework. This integration would not only streamline risk management activities but also enhance audit efficiency and organizational resilience. Establishing a closer operational relationship between OHS units and internal audit systems would contribute to safer working environments and more strategic risk oversight.